THE CONCEPTUAL ANALYSIS OF IDENTITIES AND INTERESTS IN THE THOUGHT OF ALEXANDER WENDT - Stanković, Nevena G (Politeia, 2020)
Social constructivism is usually seen as a theoretical approach that made a sociological turn in the International Relations theories, by questioning what used to be perceived as de facto truths in dominant traditional theories. In the focus of this article is the concept of identities and interests of one of the most influential theorists of constructivism, who undoubtedly inspired further theoretical debate, Alexander Wendt.However, the aim of this article is not to review, but to conceptually analyse Wendt’s theoretical approaches.  By analysing definitions of identities Wendt offers, by understanding the process of their formation (endogenous and exogenous factors), their classification (personal/corporative, identity of type, identity of role and collective identity), as well as by understanding a relation between identities and interests (complementarily explanatory role), the author attempts to highlight the theoretical contribution and potentially highly significant practical implications of Wendt’s approach, primarily to analysis of states, their interests, behaviour and, potentially, prediction about their further international relations.Furthermore, certain flaws are observed, reflected, primarily, in the existence of different, and even contradicted claims, as well as in excessive exclusivity, which are presented in an argumentative manner.  Finally, the author concludes with suggestions in order to overcome the aforementioned flaws or, to some extent, to revise Wendt’s concept of identities and interests.
Keywords: Alexander Wendt; Identity; Analysis; Interest